KOMIK ISLAMI (KOLAMI) SEBAGAI MEDIA PEMBELAJARAN AGAMA BAGI ANAK JALANAN - Alaydrus, Firza Muhammad (Jurnal al Hikmah, 2018)
Islamic Comics (Kolami) is a form of comic design that emphasizes Islamic concepts in stories that are used as learning media for street children. The Kolami story is more about the daily lives of street children by providing real examples of Islamic learning so that it is hoped that later street children will understand and want to live the Islamic religion in accordance with Islamic law and are expected to become national and religious cadres. this article will present an offer to use Islamic Comics as a learning medium for street children and experimented with street children in Lamongan.